Transthoracic versus transhiatal esophagectomy – influence on patient survival - Łochowski, Mariusz; Łochowska, Barbara; Kozak, Józef (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Aim: To evaluate the survival of patients after surgery of the esophagus/cardia using the transthoracic and transhiatal methods. Material and methods : In the years 2007–2011, 102 patients were radically treated for cancer of the esophagus/cardia: 24 women and 78 men at the average age of 59.5. There were 38 transthoracic procedures and 64 transhiatal procedures. All patients had a conduit made from the stomach, led through lodges in the esophagus and combined with the stump of the esophagus in the neck following the Collard method. Two-pole lymphadenectomies were performed in all patients. Results: Patients after transthoracic procedures had statistically more (p < 0.05) lymph nodes removed than patients after transhiatal procedures. The 5-year survival rates in transhiatal and transthoracic procedures did not statistically differ, being 8% and 0% respectively. The length of patient survival was influenced by metastases in the nearby lymph nodes (p < 0.0001) and the presence of adenocarcinoma. Conclusions : Surgical access (transhiatal and transthoracic surgery) does not affect the 5-year survival rates. Transhiatal surgery allows a greater number of lymph nodes to be removed. The main factor influencing the 5-year survival rate is the presence of metastases in the nearby lymph nodes.